FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STRES KERJA PADA ANGGOTA POLISI SATUAN RESERSE KRIMINAL POLRES BLORA - Handi Gupita Bayuwega; Ida Wahyuni; Bina Kurniawan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Occupational stress is a someone responds, either physically or mentally toward the changing in environment that distrurb and affected a person in threat. The threat that can occurs through working as a police, for example workload and salary dissatisfication. According to Indonesia Police Watch (IPW) Data showed that dozens of police commited suicide from 2011 until 2015. The result of research by National Police Headquarter concluded that 80% of criminal detective and traffic police officers experienced the occupational stress due to workloads or working pressures. This research aimed to find the related factors of occupational stress on criminal detective unit police officers in Blora district police station. The research design of this study used explanatory research with cross-sectional approach. Samples were 34 people who worked at criminal detective unit police officers in Blora district police station. The instrument of this study used questionnaire. Rank spearman statistic test used to analyze the relation between observed variables and occupational stress. The results conclude that the observed variables with related factors of occupational stress were age of respondents, career development, work relationship, in the other hands observed variables with unrelated factors of occupational stress were years of service, work demand, individual role in organization, and organizational structure and climate.